Instrument of determination and prediction of public opinion using IPTV statistic data (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Recent tendencies show an increase of information pressure on Latvia. At the moment, Latvian political figures and government persons have recognized that the country takes a hybrid war. There is a need for a new instrument of determination and prediction of public opinion. The new instrument should allow: profiling audience by identification and prediction of the rate of dissemination of information, forecasting the depth of information, forecasting how public opinion is formed, identifying and previse the adoption of the reported information. The results of the work will create a tool that a variety of institutions will be able to apply it. These institutions may be television channels, government agencies, research organizations, and others. The tool will not only accurately determine the current picture of situation, but also with high accuracy to make forecasts about the state of public opinion